Trophic transfer of microplastics in an estuarine food chain and the effects of a sorbed legacy pollutant. Issue 1 (7th January 2020) - Athey, Samantha N.; Albotra, Samantha D.; Gordon, Cessely A.; Monteleone, Bonnie; Seaton, Pamela; Andrady, Anthony L.; Taylor, Alison R.; Brander, Susanne M.
Abstract: Microplastics are of increasing concern as they are readily ingested by aquatic organisms. This study investigated microplastic trophic transfer using larval inland silversides ( Menidia beryllina ) (5 d posthatch) and unicellular tintinnid ( Favella spp.) as a model food chain relevant to North American estuaries. Low‐density polyethylene microspheres (10–20 μ m) were used to compare direct ingestion of microplastics by larval fish and trophic transfer via tintinnid prey. Dichlorodiphenyltrichloroethane (DDT)‐treated microspheres were used to determine sorbed pollutant effects on microplastic ingestion. Larval fish exposed directly to microspheres ingested significantly fewer than those exposed via contaminated prey. Larvae ingested significantly more ciliates containing DDT‐treated microspheres than ciliates containing untreated plastics but did not discriminate when exposed directly. Larvae reared for 16 d following a direct 2 h exposure had significantly lower wet weight values than unexposed controls. Our results demonstrate that trophic transfer is a significant route of microplastic exposure that can cause detrimental effects in sensitive life stages.